(untitled) (Architecture Image Studies, 2026)
This study was to identify the mediating effect of problem solving ability (PSA) on the relationship between digital literacy (DL) and clinical performance ability (CPA) in nursing students and to provide supplementary materials for developing educational programs that can bring positive changes in clinical performance by understanding the influence of these variables. The subjects were 235 nursing students conveniently sampled from a university located in W city, Gangwon-do. The results showed that problem solving ability partially mediated the relationship between subjects’ digital literacy and clinical performance ability. It indicated that the three core variables - digital literacy, problem solving ability, and clinical performance ability - were all significantly and positively correlated with one another. In-depth research is continuously needed to analyze various variables affecting the clinical performance ability of nursing students and the effects of education to improve digital literacy and problem solving ability.